Arrival of Islam in the South of Kazakhstan (Eurasian Journal of Religious Studies, 2024)
The transformation of old beliefs of Turkic people who lived in the southern regions of Kazakhstan after the arrival of Islam and the innovations that new religion brought to Turkic people will be studied in the article. In particular, in the period from the VIIIth century to the XIIIth century, the policy of the caliphates in the process of spreading Islam to the South of Kazakhstan and the problems that led to its acceptance by local nomadic people for a long time will be considered. Based on the information given on the basis of works of foreign and domestic researchers, the spread of Islamic religion in the southern regions of Kazakhstan - introduction of Islam: the period of hostility and interaction (VIII-IX centuries), the establishment of Muslim power: the spread of Islam among cities and nomads (IX-XI centuries), missionary activities of Sufi sects and widespread spread of Islam among nomads (XI-XIII centuries) are divided into three periods. In the course of the research, the differences and characteristics of religious acceptance of settled people and nomadic people will be studied and the achievements of new religion will be studied. The past and present situation of saint phenomenon among values that arrived with Islamic culture will be differentiated, and etymological meaning of concept of saint in the Holy Qur’an will be differentiated based on the translations published in the Kazakh language.Key words: Islam, saint, religion, history, South Kazakhstan.